2016
DOI: 10.1590/0100-29452016311
|View full text |Cite
|
Sign up to set email alerts
|

Water Requirement Estimate for the Reproductive Period of Mango Orchads in the Northeast of the State of Pará, Brazil

Abstract: -The aim of this study was to estimate the water consumption in mango orchard during its phenological stages in the northeastern of the State of Pará, Brazil. For this purpose, it was installed and instrumented a micrometeorological tower in a mango orchard, cv. Tommy Atkins, of 22 years old, with data collected during the crops of 2010/2011 and of 2011/2012. The actual crop evapotranspiration was estimated from the energy balance using the Bowen ratio technique. The crops were subjected to different weather c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Estimation of LE and H, as provided by the Bowen ratio method, must be consistent with the gradient-flow relationship between the components, whose β values close to − 1 may be rejected, according to the accuracy considered for the measurements, which in the present study was 0.2 ℃ for air temperature and 2% for relative air humidity (Souza et al 2016). These values were used to obtain the error-ε (Eq.…”
Section: Criteria For Rejecting Inappropriate Data From the Bowen Ratio Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…Estimation of LE and H, as provided by the Bowen ratio method, must be consistent with the gradient-flow relationship between the components, whose β values close to − 1 may be rejected, according to the accuracy considered for the measurements, which in the present study was 0.2 ℃ for air temperature and 2% for relative air humidity (Souza et al 2016). These values were used to obtain the error-ε (Eq.…”
Section: Criteria For Rejecting Inappropriate Data From the Bowen Ratio Methodsmentioning
confidence: 85%
“…The average ET c results found for the acai palm tree are similar to those found for other palm trees, such as oil palm crops in Mato Grosso, midwestern Brazil, which presented an average ET c of 3.74 mm day −1 (Viana et al 2019) and for coconut palms grown in Sergipe, northeastern Brazil, with an average ET c of 3.90 mm day −1 (Sousa et al 2011). In addition, mango crops grown near the study region, located in the eastern Amazon, presented an average ET c of 3.73 mm day −1 (Souza et al 2016).…”
Section: Evapotranspirationmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the total average annual water use was 31.63 m 3 tree −1 season −1 . De Souza et al (2016) estimated evapotranspiration rates during the mango reproductive period ranging from 402 to 420 mm, with mean daily water consumption at flowering, fruit fall, fruit formation, fruit maturation, and over the entire period of 3.8, 4.25, 3.56, 3.0, and 3.73 mm, respectively. Da Silva et al (2009) reported the accumulated evapotranspiration during two seasons ranging between 371.4 (70% ET 0 ) and 482.8 mm (100% ET 0 ).…”
Section: Water Requirementsmentioning
confidence: 99%